Unraveling doping induced anatase–rutile phase transition in TiO2 using electron, X-ray and gamma-ray as spectroscopic probes. Issue 45 (9th November 2018) - Banerjee, D.; Gupta, Santosh K.; Patra, N.; Raja, Sk Wasim; Pathak, N.; Bhattacharyya, D.; Pujari, P. K.; Thakare, S. V.; Jha, S. N.
Abstract : The present work reports the microscopic details of anatase (A) to rutile (R) phase transformation in a Mn-doped TiO2 system. Abstract : The present work reports the microscopic details of anatase (A) to rutile (R) phase transformation in a Mn-doped TiO2 system. Titanium dioxide (TiO2 ) powder was synthesized at three different dopant percentages, namely 1, 5, and 10 atom% of Mn, by a coprecipitation technique. Time differential perturbed angular correlation (TDPAC) spectroscopy was used to identify the formation of the rutile-like phase (R*) during the phase-transition process and revealed interface nucleation to be promoted by the Mn dopant. Electron paramagnetic resonance (EPR) spectroscopy, synchrotron-based X-ray absorption near edge structure (XANES), and extended X-ray absorption fine structure (EXAFS) studies showed that Mn exhibited a mixed valence states of 2+ and 4+ at different stages of the annealing process. The rutile onset temperature gradually decreased with the increase in the Mn content. The present report proposes the mechanism for the phase transformation and details the effect of Mn on the A to R phase-transformation process. This can assist in gaining a fundamental understanding of the A to R phase-transformation process and the role of the dopant in stabilizing one phase over the other.